RADIOCOMMUNICATIONS NETWORK FACILITIES - SMART POLE - Badron, Khairayu Badron (2017)
To support the deployment of transmitter sites for mobile communications and IoT applications, the smart pole concept is introduced where the physical structure of the pole can be use not only for installation of transmitter sites, but it can also support other functionalities such as surveillance, environmental sensors, digital information broadcasting, and emergency services. The use of smart poles as structures for the installation of transmitter sites represents an option for telecommunication facility providers, local councils, property developers and other relevant bodies to adopt for a greater installation density of transmitters in applicable geographic areas